Experiences of Unemployed Black People Living with Disabilities in Soshanguve Township, South Africa - An Exploratory Study - Jobodwana, Nomna Linda; Tshifhumulo, Rendani (International Journal of Criminology and Sociology, 2021)
The promise of a better life for all made by the South African government in 1994 remains unfulfilled, as many South Africans are still living in the margins of the economy where unemployment and poverty are rampant. People living with disabilities (PLWDs) are the worst affected, as they are poor with no access to jobs and housing. Despite the enactment of the Employment Equity Act (EEA) Number 55 of 1988, employment opportunities for black PLWDs are scarce in South Africa. This is due to, among other reasons, the fact that employers are reluctant to employ disabled people. This narrative study examined the experiences of black people living with disabilities (PLWDs) in Soshanguve Township, Tshwane, South Africa. It employed the symbolic interactionist (SI) theory as a lens to gain insights into the experiences of black women and men living with disabilities in their quest to access employment opportunities. The study was exploratory qualitative in nature and employed the case study design approach. Data were collected using a purposive sample of 15 black men and women living with disabilities in the Soshanguwe Township with whom in-depth interviews were conducted. This was complemented by focus group interviews with 13 purposively selected respondents who met the selection criteria. Findings were that people living with disabilities (PLWDs) were discriminated against and marginalised in employment and the workplace before and after post–apartheid South Africa. This situation leaves them inactive, economically disadvantaged and poor. The study expands knowledge on the experiences of black men and women who live with disabilities, thereby contributing towards the design of public policies and other social security interventions meant to alleviate the plight of marginalised communities in general and people living with disabilities.